Significance of S-genotype determination in the conservation of genetic resources and breeding of almond - Gómez E.M.; Dicenta F.; Batlle I.; Romero A.; Ortega E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Most almonds are self-incompatible, and they are also cross-incompatible with those having an identical incompatibility (S) genotype. In recent years, several almonds have been S-genotyped using different approaches. This information has been included in different tables of cross-incompatibility groups, which are an update of the previously proposed one. However, no attempt has been made to reconcile the information of all these tables neither to correct possible inconsistencies. In this work we have determined the S-genotype of 15 Spanish almond cultivars previously un-genotyped using consensus primers for the first and second introns of Prunus S-RNases, and also allele-specific primers here designed. We could identify a new S-RNase allele numbered as S51, which was cloned and sequenced. With the information obtained in this work and in previous studies, we have established eight new cross-incompatibility groups. Some of the already proposed groups need to be re-numbered to avoid the gaps left by those no longer existing. The determination of the S-genotype of almond genetic resources to be preserved as part of the agricultural biodiversity will facilitate the use of this material in research and breeding, and also provides useful information about phylogenetic relationships.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)